Visual Word Expertise: A Study of Inversion and the Word-Length Effect, with Perceptual Transforms. (May 2014) - Björnström, Laura Eklinder; Hills, Charlotte; Hanif, Hashim; Barton, Jason J S
The word-length effect may indicate whether reading is proceeding in an efficient whole-word fashion or by serial letter processing. If it is an index of an orientation-dependent expert reading mechanism, then it should show an inversion effect, with a large difference between upright and upside-down text that is specific for normally configured text. We measured response time of healthy subjects reading 3- to 9-letter words presented in normal configuration, in mirror reflection or spelt backward, in either upright or inverted orientation. The word-length effect showed an inversion effect specific for normal text, as it was not seen for either backward or mirrored text, a result that differed from that for simple mean response times. Also, the word-length effect was smaller for backward than for mirrored text, suggesting that reading of transformed text uses primarily local letters rather than global word forms. We conclude that the word-length effect is a suitable index of expert reading, and reveals that reading under perceptually difficult conditions relies on a sublexical letter-based strategy.